In search of international tort law : civil liability of arms manufacturers for indirect sales to embargoed conflict zones - Lorite, Alejandro (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2007.